The Implementation Of The ICT-Based Thesis Supervision At One Of Postgraduate Programs In Indonesia - Ujang Suparman (Bandar Lampung University (UBL), 2013)
The development of information, computer and technology (ICT) has affected all sectors and activities including education from elementary school through university. However, even though the use of ICT has been widespread including in the University, its use in thesis supervision processes is still very limited. Only few lecturers have used it optimally. By contrast, many students and lecturers in certain universities get difficulties in determining an appropriate time for both parties because of the business of either lecturers or students. This study is intended to find out a new effective and efficient strategy to supervise students writing thesis in a postgraduate program and to investigate the implementation of the ICT-based thesis supervision. Therefore, there are three major objectives of the research: 1. To investigate how to implement the ICT-based thesis supervision; 2. To trace the opinion of Masters students of English Education Program on the implementation of the ICT-based thesis supervision; and 3. To find a new effective way of thesis supervision. The research is qualitative bynature. The data were gathered by means of questionnaire, interview, and documents. Based on the data analysis and discussion, some conclusions are drawn. It has been found that the use of ICT in supervising students writing theses was very effective, and efficient. The students and lecturer are not limited by space and time, that is, they can communicate by means of internet anytime and anywhere; the advice that the supervisors provide is easily understandable and very neat. The students feel easy to follow what the supervisorsuggests. And what is more important is that the students writing products are much better, more comprehensive, and neater.